Effect of Early Psychological Counseling for the Prevention of Posttraumatic Stress Induced by Acute Coronary Syndrome at Long-Term Follow-Up - Princip, Mary; Pazhenkottil, Aju P.; Barth, Jürgen; Schnyder, Ulrich; Znoj, Hansjörg; Schmid, Jean-Paul; Langraf-Meister, Rebecca E.; von Känel, Roland; Ledermann, Katharina (Frontiers in Psychiatry, 2022)
OBJECTIVE: Psychological consequences of myocardial infarction (MI) are substantial, as 4% of all MI patients develop posttraumatic stress disorder (PTSD) and 12% clinically relevant posttraumatic stress symptoms (PTSS). The study investigated the course and development within 12 months of MI-induced PTSS to gain novel insights in potentially delayed response to early trauma-focused counseling aimed at preventing the incidence of MI-induced PTSS. METHODS: In the MI-SPRINT two-group randomised controlled trial, 190 MI-patients were randomly allocated to receive a single-session intervention of either trauma-focused counselling or an active control intervention targeting the general role of stress in patients with heart disease. Blind interviewer-rated PTSS (primary outcome) and additional health outcomes were assessed at 12- month follow-up. RESULTS: 12-month follow-up of outcomes were available for 106 (55.8%) of 190 participants: In the entire sample, one patient (05%, 1/190) who received trauma-focused counseling developed full PTSD. There was no significant difference between trauma-focused counseling and stress counseling regarding total score of interviewer-rated PTSS (p>0.05). The only group difference emerged in terms of more severe hyperarousal symptoms in the trauma-focused counseling group in the ITT analysis, but not in the completer analysis. CONCLUSIONS: No benefits were found for trauma-focused counseling after 12 months when compared with an active control intervention. PTSD prevalence in the present study was low highlighting a potential beneficial effect of both interventions. Further studies are needed to determine the most accurate approach of counseling.